2012
DOI: 10.1186/1471-2229-12-22
|View full text |Cite
|
Sign up to set email alerts
|

The cold-induced basic helix-loop-helix transcription factor gene MdCIbHLH1encodes an ICE-like protein in apple

Abstract: BackgroundPlant growth is greatly affected by low temperatures, and the expression of a number of genes is induced by cold stress. Although many genes in the cold signaling pathway have been identified in Arabidopsis, little is known about the transcription factors involved in the cold stress response in apple.ResultsHere, we show that the apple bHLH (basic helix-loop-helix) gene MdCIbHLH1 (Cold-Induced bHLH1), which encodes an ICE-like protein, was noticeably induced in response to cold stress. The MdCIbHLH1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 38 publications
3
114
0
Order By: Relevance
“…Two bHLH transcription factors, Sb06g025040 and Sb06g0254060 belong to an anthocyanin regulatory mechanism and were associated with the anthocyanin levels measured under cold conditions. Transcription factors such as bHLH are suggested to be involved in stress-adaptive mechanisms; recent studies have shown the role of such transcription factors at least in part to cold tolerance, by positively regulating ROS removal [4143]. Similarly, Sb03g031320, a C2H2 zinc finger protein with a putative splicing function, is associated with root fresh weight under cold conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Two bHLH transcription factors, Sb06g025040 and Sb06g0254060 belong to an anthocyanin regulatory mechanism and were associated with the anthocyanin levels measured under cold conditions. Transcription factors such as bHLH are suggested to be involved in stress-adaptive mechanisms; recent studies have shown the role of such transcription factors at least in part to cold tolerance, by positively regulating ROS removal [4143]. Similarly, Sb03g031320, a C2H2 zinc finger protein with a putative splicing function, is associated with root fresh weight under cold conditions.…”
Section: Resultsmentioning
confidence: 99%
“…MdbHLH104 protein levels were determined by protein gel blotting using an anti-GFP or anti-MYC antibody as described previously (Feng et al, 2012). Protein extracts were separated on a 12% SDS-PAGE gel and transferred to polyvinylidene difluoride membranes (Roche) using an electrotransfer apparatus (Bio-Rad).…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
“…• C (Feng et al, 2012). Upregulation of MdCIbHLH1 was also followed by an increased expression of the five apple CBFs (MdCBF1, MdCBF2, MdCBF3, MdCBF4 and MdCBF5) during the low temperature exposure and the MdCIbHLH1was shown to bind to an AtCBF3 promoter MYC4 site.…”
Section: Bmentioning
confidence: 99%